STRATEGIC EXPORT MARKETING PLAN OF DEAKIN UNIVERSITY - Cut Aprilia (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2012)
This is a case study of Deakin University that will expand their education service to Turkey. Turkey is located in Southeastern Europe and Southwestern Asia with a strong growing economy, population and demand for tertiary education. It presents a good opportunity for Deakin University to expand its education services in and increase its market share globally. Considering the high level interests amongst Turkish students in the field of Business, Deakin will offer a Business degree in Commerce where students can further specialize in various fields. In doing so, Deakin will be in partnership with a local university called Koc University.  Located in Istanbul, where the majority of the target market is concentrated, Koc University has the facilities that Deakin can use in providing education services in Turkey. On the other hand, Deakin will provide the information technology equipments, Deakin Student Online (DSO) systems and learning resources such as access to Journals, online live conference etc. Highly qualified lecturers, both from Australia and local teachers will be help to ensure the quality of teaching learning process provided by Deakin.  In addition, Deakin has an extensive experience in providing education services abroad through partnerships, often called offshore programs, and will use its experience for its expansion to the education market in Turkey. Despite having seven agents in Turkey, Deakin is currently relatively unknown to the Turkish education market. In order to promote the marketing activities in Turkey as well as support the students enrolled at the offshore program, Deakin will open a representative office. Considering the large market in the high school student segment and the education situation in Turkey where there is more demand of tertiary education than university places, there is a high opportunity of success for Deakin in Turkey. Keywords: Deakin University, Turkey, International Marketing, Education service